Symbolic power in caricature of Nigerian academia in selected videos of Sagacious Prof - Temitope Michael Ajayi; Tayo Adebayo; David Oluwatobi Esuola (Yayasan Mitra Persada Nusantara, 2025)
Caricature, often visual, involves exaggerations for satirical, critical, or comic effect. Scholarly probes on caricature have focused on political and legal contexts with less attention to academia. Particularly, there is a dearth of symbolic power studies detailing the power relations between participants in Nigerian academia. The present study, therefore, explores how Facebook content creator, Sagacious Prof, depicts systemic issues in academia, with reference to the Nigerian context, examining how academics deploy linguistic choices to negotiate unethical goals in student-lecturer interactions. Adopting a qualitative approach, the study analysed ten purposively sampled videos of Sagacious Prof, whose content primarily depicts activities within the Nigerian academic context. The data analysis is guided by Norman Fairclough’s (1995) Critical Discourse Analysis. The findings showcased two negative systemic issues in Nigerian academia: transactional grading and transactional sex. By implication, Nigerian academics are largely constructed as being unethical in their engagements with students in the skits of Sagacious Prof.